Perancangan Aplikasi Penjualan Online Daur Ulang Sampah Berbasis Android - Sigit Hudawiguna; Aat Aat; Sri Rahayu (Jurnal Algoritma, 2022)
The Garut Regency Environmental Service has a waste management or waste recycling site where waste is turned into a product such as organic fertilizer and product bags, carpets, flower vases, and other handicrafts that are useful and have a sale value. With the help of the creative community, waste can be managed and distributed into a product such as handicrafts or compost, resulting in a profitable business process for the community. The current obstacle in the field is the absence of marketing media to offer recycled products to the general public so craftsmen experience difficulties in promoting their craft products. The purpose of this research is to design an Android-based online recycling application. The methodology used in designing an Android-based online waste recycling sales application uses the USDP (Unified Software Development Process) methodology. The results of this study produce an android-based online waste recycling sales application that can be used as a facility to become a media for marketing and selling recycled waste so that business processes that occur can run smoothly.